Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques